2018
DOI: 10.1017/ice.2018.62
|View full text |Cite
|
Sign up to set email alerts
|

Patient Involvement in Healthcare-Associated Infection Research: A Lexical Review

Abstract: OBJECTIVEThis review examines patient involvement in healthcare-associated infection (HAI) research. Healthcare-associated infections represent an intractable issue with considerable implications for patients and staff. Participatory methodologies that involve patients in healthcare research are associated with myriad benefits.DESIGNLexical review.METHODSPubMed was searched to identify all publications on patient involvement in HAI research since 2000; publications were also identified from the cited reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Fourteen papers from the international literature search were reviewed (table 3), six5 6 9–11 of which were literature reviews (eg, systematic, lexical and integrative), six studies7 19 21–26 28 that used qualitative approaches (eg, individual interviews and focus groups), one quasi-experimental study20 and an expert panel report 18…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fourteen papers from the international literature search were reviewed (table 3), six5 6 9–11 of which were literature reviews (eg, systematic, lexical and integrative), six studies7 19 21–26 28 that used qualitative approaches (eg, individual interviews and focus groups), one quasi-experimental study20 and an expert panel report 18…”
Section: Resultsmentioning
confidence: 99%
“…Transmission of HCAI through the contamination of patients’ hands, for example, is as important as contamination of HCP’s hands 11. However, the majority of studies have been focused only on strategies to encourage patients to ask HCPs about their compliance with standard precautions,5–7 9 11 18 20 21 undermining the development of a patient’s own accountability for IPC. Only three studies were identified that reported strategies to encourage patients to monitor themselves in IPC22 26 28; for example, with patient-to-patient education.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations